Legal Compliance of Acehnese Muslim Society in Technological Disruption Era: Study of Online Gambling and Prostitution - Helmi, Muhammad Ishar; Pujiyono; Khamami; Hidayat, Asep Syarifuddin (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2025)
Technological developments have significantly impacted the legal culture of Acehnese Muslim society, particularly through the rise of online gambling and prostitution. As a region with special autonomy to implement Islamic law, Aceh enforces the Qānūn Jināyah based on Sharia principles. However, the increasing accessibility of digital platforms has facilitated immoral practices, challenging both legal enforcement and cultural norms. This study aims to analyze: (1) Aceh law enforcement in facing the rise of new criminal cases, namely online gambling and prostitution, and (2) Challenges and opportunities to maintain legal compliance amidst technological development. Using a socio-legal approach with qualitative methods, the research collected primary data through interviews with law enforcement officials, community members, and individuals involved in technology-based crimes. The findings reveal that despite the existence of Sharia-based laws, enforcement remains ineffective due to social, economic, and institutional limitations. Applying Lawrence Friedman’s legal system theory—substance, structure, and culture—the study concludes that while the legal framework is in place, societal support and institutional consistency are lacking. This research contributes to the discourse on Islamic law enforcement in the digital era and highlights the urgency of policy reform to address technology-based crimes more effectively within Sharia frameworks.